The longer the antithyroid drug is used, the lower the relapse rate in Graves’ disease: a retrospective multicenter cohort study in Korea - Park, So Young; Kim, Bo Hyun; Kim, Mijin; Hong, A.Ram; Park, Jun; Park, Hyunju; Choi, Min Sun; Kim, Tae Hyuk; Kim, Sun Wook; Kang, Ho-Cheol; Chung, Jae Hoon (Endocrine, 2021)
Purpose Current literature suggests 12–18 months of antithyroid drug (ATD) treatment for patients with Graves’ disease, but the risk of relapse is high. Although some studies reported better outcomes of long-term ATD treatment, recent data that suggest the optimal treatment duration are limited. Methods We performed a multicenter retrospective cohort study of 908 patients newly diagnosed with Graves’ disease between 2006 and 2013. The relapse rate according to ATD treatment duration was analyzed. Results After initial ATD treatment, 338 patients (37.2%) had relapsed. The relapse rate according to ATD treatment duration was 42.4% at 1 year, 38.5% at 2 years, 33.8% at 3 years, 31.7% at 4 years, 30.2% at 5 years, 27.8% at 6 years, and 19.1% at more than 6 years, respectively, demonstrating a significant decreasing trend ( p = 0.003). In a multivariable Cox regression analysis, ATD treatment duration was an independent risk factor for relapse ( p = 0.043). Conclusions The longer that ATD therapy is used, the lower the relapse rate is in patients with Graves’ disease. Long-term ATD treatment may be considered in Graves’ patients who do not show complications or an economic burden from hyperthyroidism.